(untitled) (Journal of Applied Learning and Teaching, 2024)
As the 2020s march on into a post-COVID age, an increasing trend for academics to exit their current academic positions or to leave academia altogether can be observed internationally and locally. Consequently, a sizeable body of experts accessible to higher education but geographically beyond its ivory towers and psychologically outside its neoliberal grip has come to exist. These para-academics and public intellectuals continue to contribute to communities of teaching, learning, and researching but do so often without affiliation. This study explores the relational link between the archaic notion of affiliation and what it means to ‘belong’ to a university as staff. The study problematises belonging as an assimilative designator of an organisation’s culture and suggests that belonging, as employed in teaching and learning discourse, as a trust-based mode of building community, is a different beast than that conceived by neoliberal universities. Using vignettes as narrative enquiry, the paper retells and curates six accounts of academics making transitions out of academic positions and finding fresh educational contexts for belonging. These emancipatory narratives move through spaces of trauma into authentic places of reclaimed identity, most notably as independent public intellectuals within a broader context of global citizenship. The narratives show us what life after being academically affiliated can look like when individuals exercise critical resilience to establish academic identities beyond the neoliberal university.